Managing Water equitably for Agriculture in Sub-Saharan Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
This summary report outlines the seminar approach and the problems relating to the development of irrigation..